2022
DOI: 10.3389/fpls.2022.883720
|View full text |Cite
|
Sign up to set email alerts
|

Full-Length Transcriptome Sequencing and Comparative Transcriptomic Analyses Provide Comprehensive Insight Into Molecular Mechanisms of Cellulose and Lignin Biosynthesis in Cunninghamia lanceolata

Abstract: Cunninghamia lanceolata is an essential timber species that provide 20%–30% raw materials for China’s timber industry. Although a few transcriptomes have been published in C. lanceolata, full-length mRNA transcripts and regulatory mechanisms behind the cellulose and lignin biosynthesis have not been thoroughly investigated. Here, PacBio Iso-seq and RNA-seq analyses were adapted to identify the full-length and differentially expressed transcripts along a developmental gradient from apex to base of C. lanceolata… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

0
5
0

Year Published

2022
2022
2024
2024

Publication Types

Select...
4
1
1

Relationship

1
5

Authors

Journals

citations
Cited by 6 publications
(5 citation statements)
references
References 60 publications
0
5
0
Order By: Relevance
“…In rice, Sun et al found that DROT1 can improve drought tolerance, mainly by regulating the cell wall fiber content and crystal structure in microtubule tissues to enhance drought resistance (Sun et al, 2022). Du et al found that TaERF87 (ethylene response factor (ERF)) could interact with TaAKS1 to enhance the expression of TaP5CS1 and TaP5CR1, thus improving proline synthesis and drought resistance in wheat (Du et al, 2022). Through a GWAS in maize, it was found that three SNP mutations in ZmSRO1d significantly increased the reactive oxygen species (ROS) content of guard cells, promoted stomatal closure, enhanced drought resistance, and increased the yield of overexpressed ZMSRO1D-R by 60% compared with that in the control .…”
Section: Discussionmentioning
confidence: 99%
“…In rice, Sun et al found that DROT1 can improve drought tolerance, mainly by regulating the cell wall fiber content and crystal structure in microtubule tissues to enhance drought resistance (Sun et al, 2022). Du et al found that TaERF87 (ethylene response factor (ERF)) could interact with TaAKS1 to enhance the expression of TaP5CS1 and TaP5CR1, thus improving proline synthesis and drought resistance in wheat (Du et al, 2022). Through a GWAS in maize, it was found that three SNP mutations in ZmSRO1d significantly increased the reactive oxygen species (ROS) content of guard cells, promoted stomatal closure, enhanced drought resistance, and increased the yield of overexpressed ZMSRO1D-R by 60% compared with that in the control .…”
Section: Discussionmentioning
confidence: 99%
“…The lignin biosynthesis pathway is a complex process involving many biological events that are strictly regulated by various genes [ 19 ]. Lignin monomer synthase genes, including PAL , 4CL , COMT , HCT , CSE , CCR , CAD , and POD , have been investigated in Arabidopsis thaliana [ 20 , 21 ], Populus [ 22 ], and Cunninghamia lanceolata [ 23 ]. PAL is the first enzyme-encoding gene involved at the beginning of this pathway, and it determines the metabolic flow of the entire pathway [ 24 ].…”
Section: Discussionmentioning
confidence: 99%
“…Using poly-T oligo-attached magnetic beads, mRNA was extracted from total RNA. cDNA synthesis was implemented following our previous research (Hu et al, 2022). RNA sequencing was implemented by using Illumina NovaSeq 6,000 platform and 150 bp paired-end raw reads were generated.…”
Section: Rna Isolation Library Construction and Sequencingmentioning
confidence: 99%
“…qRT-PCR was implemented with the TB Green Premix Ex Taq II (Tli RNaseH Plus; Takara) on CFX96 real-time PCR detection system (CFX96; Bio-Rad, United States). The expression pattern was assessed by our previous protocol (Hu et al, 2022). For each gene and sample, the qRT-PCR data were acquired from three biological and three technical repeats.…”
Section: Quantitative Rt-pcr Analysismentioning
confidence: 99%